Analysis of Critical Thinking Skills of Prospective Elementary School Teacher Student - Julianto, Julianto; Wiryanto, Wiryanto; Suprayitno, Suprayitno; Susetyo R, Asri; Hidayati, Fitria; Rahmawati, Endah (IJORER : International Journal of Recent Educational Research, 2023)
Objective: Education is one of the basic needs of humans. The current educational challenge is to produce individuals who can compete in the 21st century. We can access various information freely via the internet, and there is no guarantee that the news we see is true. To use this information properly, individuals must evaluate data and information sources. Method: The type of research used is qualitative research. The population in this study is all ESTE FoE Unesa students, and the sample used is the 2018-2020 class. The sample used was class 2019, D, and F, totaling 84 students. The data collection method used in this study is the test. The instrument used in this study was a critical thinking skills test. Data analysis was carried out in percentage terms. Results: The results showed that the critical thinking skills of Elementary School Teacher Education Faculty of Education Unesa students were in a low category. The results of this study are expected to be used by lecturers or researchers to design and develop learning activities that can facilitate students to practice critical thinking skills. Novelty: Lecturers can design the implementation of learning in the classroom that trains critical thinking skills to become more qualified, effective, and efficient.